2021
DOI: 10.1007/s12035-020-02276-8
|View full text |Cite|
|
Sign up to set email alerts
|

Genomic Action of Sigma-1 Receptor Chaperone Relates to Neuropathic Pain

Abstract: Sigma-1 receptors (Sig-1Rs) are endoplasmic reticulum (ER) chaperones implicated in neuropathic pain. Here we examine if the Sig-1R may relate to neuropathic pain at the level of dorsal root ganglia (DRG). We focus on the neuronal excitability of DRG in a “spare nerve injury” (SNI) model of neuropathic pain in rats and find that Sig-1Rs likely contribute to the genesis of DRG neuronal excitability by decreasing the protein level of voltage-gated Cav2.2 as a translational inhibitor of mRNA. Specifically, during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 71 publications
(99 reference statements)
0
6
0
Order By: Relevance
“…Such a reduction in KCl depolarization fits with our observations. However, the notion that sigma-1 affects sensory neurons primarily through the modulation of voltage-gated Ca 2+ channels does not fit as well with our observed effects of barbamide on SOCE [ 23 ].…”
Section: Discussionmentioning
confidence: 85%
“…Such a reduction in KCl depolarization fits with our observations. However, the notion that sigma-1 affects sensory neurons primarily through the modulation of voltage-gated Ca 2+ channels does not fit as well with our observed effects of barbamide on SOCE [ 23 ].…”
Section: Discussionmentioning
confidence: 85%
“… Schematic illustration of the model of the signaling mechanism. SIGMAR1/Sigma-1 receptor translocates from the endoplasmic reticulum (ER) to nuclear membrane when cells are under stressful conditions [ 83 ]. ( A ) When motor neurons are under the insult of toxic (G4C2)RNA repeats upon their nuclear pore proteins [ 13 ], POM121 cannot recruit KPNB1/importinβ1 for the nuclear import of transcription factor TFEB.…”
Section: Resultsmentioning
confidence: 99%
“…This response seems to be enhanced in transgenic mice with overexpressed 4E-BP1, which is part of the mTOR pathway and therefore plays a fundamental role in the control of pro-survival gene transcription [25]. Wang et al observed that the knock-out of SIGMAR1 in human embryonic kidney 293T cells decreased the expression of 4E-BP1, which suggests that SIGMAR1 does not only affect UPR from the ER but also from the mitochondria, since 4E-BP1 can impact UPRm [26]. Finally, Mori et al observed that, like SIGMAR1, IRE1 is enriched at the MAM in Chinese hamster ovarian cells.…”
Section: The Relevance Of the Unfolded Protein Response (Upr) In Neur...mentioning
confidence: 99%
“…Figure1. Innate resilience provided by SIGMAR1 from head to tail against neurodegeneration[4,22,26,39,47,48,52,61,62,64,66,[68][69][70][71][72]75,78].…”
mentioning
confidence: 99%